Passiflora mollissima Seed Extract Induced Antiproliferative and Cytotoxic Effects on CAL 27 Spheroids - Angela Fonseca-Benitez; Sandra Johanna Morantes Medina; Diego Ballesteros-Vivas; Fabian Parada-Alfonso; null Sandra J Perdomo (Advances in Pharmacological and Pharmaceutical Sciences)
Multicellular tumor spheroids are used as models in drug development due to their characteristics simulating in vivo tumors. Likewise, antiproliferative properties of extracts derived from fruits have been widely described. Peels and seeds can be used as a matrix to obtain different compounds. Recently, a study demonstrated the antiproliferative activity from a P. mollissima extract (PME) on human colon cancer cells; however, its effect on oral spheroids is unknown. Objective. To evaluate the antiproliferative potential of an extract obtained from P. mollissima seeds on the spheroid-type-3D culture model of CAL 27. Methods. CAL 27-spheroids were treated with three concentrations of PME (10, 50, and 100 μg/ml). After 72 hr incubation, morphology and cellular changes, cytotoxic and proapoptotic effect, gene expression, and metastasis were determined. Additionally, changes in the cell cycle phases responded to the PME concentrations. Comparisons between groups were made through a U Mann-Whitney test. Results. It was shown that 100 μg/ml PE affects CAL 27 cells proliferation grown in spheroids through cell cycle arrest and gene regulation of p53, HIF 1α, and CDH1. However, none of the treatments employed induced MMP9 gene expression. Conclusion. Our study shows that PME inhibits the growth and proliferation of oral tumor cells cultured in spheroids through the positive regulation of cell death and metastasis genes.